Estradiol vaginal inserts (4 µg and 10 µg) for treating moderate to severe vulvar and vaginal atrophy: a review of phase 3 safety, efficacy and pharmacokinetic data. (2nd December 2018) - Constantine, Ginger D.; Simon, James A.; Pickar, James H.; Archer, David F.; Bernick, Brian; Graham, Shelli; Mirkin, Sebastian
Abstract: Objective: To review safety, efficacy and pharmacokinetic (PK) data from the phase 3 REJOICE trial, which evaluated a 17β-estradiol (E2) softgel vaginal insert approved in 2018 for moderate to severe dyspareunia associated with menopausal vulvar and vaginal atrophy (VVA). Methods: REJOICE (Clinicaltrials.gov: NCT02253173) was a randomized, double-blind, placebo-controlled trial in which women with moderate to severe dyspareunia due to menopausal VVA received 4 µg, 10 µg or 25 µg of an E2 vaginal insert or placebo for 12 weeks. The published data for the recently approved 4 µg and 10 µg doses of the E2 vaginal insert, including four co-primary efficacy endpoints (change from baseline to week 12 in percentages of superficial and parabasal cells, vaginal pH and severity of dyspareunia), safety and PK (which included serum E2 levels measured by gas chromatography and tandem mass spectrometry), are summarized here. Results: Women were randomized to receive the E2 vaginal insert (4 µg [ n  = 186] or 10 µg [ n  = 188]; Imvexxy a ) or placebo ( n  = 187) in the modified intention-to-treat population. The E2 vaginal insert (4 µg and 10 µg) significantly improved the percentages of superficial and parabasal cells ( p  < .0001), vaginal pH ( p  < .0001), and the severity score for dyspareunia ( p  < .05) from baseline to week 12 compared with placebo. The recently approved E2 vaginal insert was well tolerated, with no clinically significant differences in treatment-emergent or serious adverse events versus placebo. Systemic absorption of E2 with both doses was minimal. Conclusions: The recently FDA-approved E2 softgel vaginal insert (4 µg and 10 µg) was safe and effective over 12 weeks for treating moderate to severe dyspareunia due to menopausal VVA with minimal systemic E2 levels.